Recent Advances in the Synthesis of Biologically Relevant Selenium-containing 5-Membered Heterocycles - Rafique, Jamal; F. S. Canto, Romulo; Saba, Sumbal; A. R. Barbosa, Flavio; L. Braga, Antonio (Current Organic Chemistry, 2016)
Organoselenium compounds are molecules with important potential therapeutic applications. Seleniumcontaining 5-membered heterocycles have emerged as an important class of biological compounds. In the past five years, several articles related to the design, synthesis and biological evaluation of these compounds have been published. These heterocycles have been applied as antioxidants, cytotoxic agents, apoptosis inducers and chemopreventors, and they possess antidepressant activity, among others. This review describes the methodologies involved in the synthesis of biologically significant selenium-containing 5-membered heterocycles from 2010 to the present.
Keywords: antioxidant